Mechanisms of resistance to acetolactate synthase-inhibiting herbicides in populations of Apera spica-venti from the Czech Republic - Hamouzová, Kateřina; Košnarová, Pavlína; Soukup, Josef; Hamouz, Pavel (Pest management science, 2014)
BACKGROUND: This study investigates the mechanisms of resistance to acetolactate synthase-inhibiting herbicides in populations of Apera spica-venti (L.) P.B. from the Czech Republic. RESULTS: The proportion of resistance due to mutant acetolactate synthase (ALS) alleles was estimated by genotyping individuals from each of three populations for the eight ALS mutations known to confer resistance. Four resistance-conferring ALS mutations were identified: Pro-197-Ala, Pro-197-Thr, Trp-574-Leu and previously unreported Trp-574-Met substitution. Two populations (R1, R3) have amino acid substitution at positions Pro-197 and Trp-574. Individuals from the R3 population had two different resistance alleles. In the R2 population, only the resistant Trp-574-Met substitution was detected. Ten other single point mutations were identified, but these were not related to resistance. The cytochrome malathion decreased chlorsulfuron resistance in the resistant populations that were examined. Although malathion increased mortality, the GR50 values were too high to conclude that non-target-based mechanism was the main one for the resistance in Apera spica-venti populations tested in this study. CONCLUSIONS: Individuals of Apera spica-venti populations tested in this study possess the target-site ALS resistance mutation and an additional so far unknown resistance mechanism(s).
Keywords: Base Sequence; DNA, Plant; Enzyme Inhibitors; Molecular Sequence Data; Sulfonamides; malathion; fyziologická adaptace; Malathion; Poaceae; Triazines; Herbicide Resistance; acetolaktátsynthasa; molekulární sekvence - údaje; Czech Republic; sulfonamidy; lipnicovité; inhibitory enzymů; DNA rostlinná; sekvence nukleotidů; Adaptation, Physiological; Acetolactate Synthase; rezistence k herbicidům; triaziny; Česká republika